Comparative Analysis of Accrual and Cash Accounting Methods in Financial Reporting - Rangkuti, Lusi Elviani; Suboh, Amerruddin Shah (East Asian Journal of Multidisciplinary Research, 2024)
This study examines the comparative analysis of accrual and cash accounting methods in financial reporting. Accrual accounting, which records revenues and expenses when they occur, provides a comprehensive and accurate depiction of a company’s financial health. It is preferred by larger companies and those requiring compliance with accounting standards such as GAAP and IFRS. Conversely, cash accounting records transactions only when cash changes hands, offering simplicity and ease of use, making it suitable for small businesses and individuals. Despite its straightforward nature, cash accounting may not fully represent a company's financial commitments and resources. The choice of accounting method influences financial reporting accuracy, complexity, compliance, and strategic decision-making. This study highlights the strengths and limitations of each method, providing insights for businesses to select the appropriate approach based on their size, complexity, and stakeholder requirements.